OP0235 Interferon-free antivirals for hepatitis c virus-associated cryoglobulinemia vasculitis: a long-term follow-up study. (12th June 2018) - Cacoub, P.; Si ahmed, S.N.; ferfar, Y.; Pol, S.; Thabut, D.; Hezode, C.; Alric, L.; Comarmond, C.; Ragab, G.; Quatuccio, L.; Hegazy, M.; Poynard, T.; et al.
Abstract : Background: In small-size and short term studies of hepatitis C virus (HCV)-cryoglobulinemia vasculitis (CryoVas), direct antiviral agents (DAAs) showed a better response rate and tolerance than interferon containing regimens. Objectives: To evaluate the effectiveness and tolerance of all oral interferon-free DAA in a large CryoVas cohort with long-term follow-up. Methods: This prospective international multicenter cohort study included 148 symptomatic HCV-CryoVas patients (53.7% with cirrhosis and 49.3% antiviral-naïve). They all received DAA, i.e. sofosbuvir (SOF) plus daclatasvir (n=53), SOF plus ribavirin (n=51), SOF plus ledipasvir (n=23), or SOF plus simeprevir (n=18), for 12 or 24 weeks. The primary endpoint was the clinical response of CryoVas symptoms at week 12 after stopping DAAs. Results: 106 (72.6%) patients showed a complete response, 33 (22.6%) a partial response and 7 (4.8%) no response of CryoVas symptoms. Cryoglobulinemia was no longer found in 53.1%. A sustained virological response was obtained in 97.2%. Premature DAA withdrawal was noted in 4.1%. Two factors were associated with a poor response: a severe form of CryoVas [OR 0.33, 95% CI: 0.12 to 0.91; p=0.03] and peripheral neuropathy [OR 0.31, 95% CI: 0.11 to 0.84; p=0.02]. After a median follow-up of 15.3 months, 4 (2.8%) patients died. The final clearance rates of CryoVas manifestations were as follows: purpura (97.2%), renal involvement (91.5%), arthralgia (85.7%), neuropathy (77.1%) and cryoglobulinemia (53.8%). Only SOF plus ledipasvir regimen showed significant superiority [OR 4.09, 95% CI: 1.19 to 19.00; p=0.04]. Conclusions: The different DAA combinations showed high response rates of HCV-CryoVas symptoms. The tolerance was good, and the mortality rate was very low. We identified prognosis factors of response to DAA. Disclosure of Interest: P. Cacoub Consultant for: Janssen, BMS, Abbvie, GSK, Astra zeneka, Gilead, Merck, Roche, Servier, Vifor, S. N. Si ahmed Consultant for: BMS, Abbvie, Gilead, Roche, Janssen, Y. ferfar: None declared, S. Pol Consultant for: Sanofi, Novartis, Vertex, Boehringer, Janssen, BMS, Abbvie, GSK, Astra zeneka, Gilead, Merck, Roche, Servier, Vifor, D. Thabut: None declared, C. Hezode Consultant for: BMS, Merck, Abbvie, Gilead, Roche, Janssen, L. Alric Consultant for: BMS, Abbvie, Gilead, Janssen, Merck, C. Comarmond: None declared, G. Ragab: None declared, L. Quatuccio: None declared, M. Hegazy: None declared, T. Poynard: None declared, M. Resche Rigon: None declared, D. Saadoun Consultant for: medimmune, BMS, Abbvie, GSK, Astra zeneka, Gilead, Merck, Roche, Servier,